(untitled) (Biological Sciences - PJSIR, 1995)
In a pot experiment, 8 wheat varieties were compared for N partitioning at anthesis and maturity to study the sig- nificance of preanthesis and postanthesis N uptake and postanthesis dry matter accumulation in determining grain yield, grain N yield and grain nitrogen concentration (ONC). The wheat varieties (Lu-26, Sind-8l, Pak-81, Durum, Punjab- 85, Fbd-85, Sarsabz and M-143) were grown with and without appl ying fertilizer N. Varietal differences were observed for N uptake and response to applied N. However, the efficiency ofN translocation from shoot to grain during maturation was almost identical in all the varieties except for Punjab-85, which showed lower translocation, but derived a higher amount of N from soil after anthesis. Remobilization of vegetative N ranged between 74 and 85% in different varieties at the two N levels. However, substantial quantities of N were also taken up after anthesis. The amount of this N was much higher in fertilized than in unfertilized plants. The results of this study suggested the both pre and post-anthesis N uptake are important in influencing the grain yield.